2012
DOI: 10.1007/s10545-012-9559-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain magnetic resonance imaging findings in patients with mucopolysaccharidosis VI

Abstract: MPS VI patients may present abnormal IQ scores without correlation with brain abnormalities on the MRI, a finding which was found to be very frequent in MPS VI. Additional studies are required to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…Patients with MPS I, II, III, and VII may also exhibit learning difficulties and neurological decline [1]. Although MPS IV and VI are generally considered not to affect neurocognitive development, some patients may have an IQ below the normal range [3,4]. It remains to be elucidated if this is a direct result of the disease or indirectly results from reduced school attendance or [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MPS I, II, III, and VII may also exhibit learning difficulties and neurological decline [1]. Although MPS IV and VI are generally considered not to affect neurocognitive development, some patients may have an IQ below the normal range [3,4]. It remains to be elucidated if this is a direct result of the disease or indirectly results from reduced school attendance or [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in a recent study of 25 MPS VI patients, approximately 30 percent had IQ scores below the normal range (69 or lower) (20). As brain abnormalities on MRI did not correlate with IQ scores, the investigators suggested that cultural deprivation and physical limitations associated with the disease (fatigue, and visual or hearing deficits) may have an impact on the outcome of IQ testing in these patients (20).…”
Section: Clinical Features Of Mps VImentioning
confidence: 99%
“…Although several studies have shown abnormalities in the central nervous system of patients with MPS VI, including abnormalities in the ventricular system, white matter and perivascular spaces, communicating hydrocephalus, and cerebral atrophy (18)(19)(20), MPS VI is generally considered not to affect intellectual development. Nevertheless, in a recent study of 25 MPS VI patients, approximately 30 percent had IQ scores below the normal range (69 or lower) (20).…”
Section: Clinical Features Of Mps VImentioning
confidence: 99%
See 1 more Smart Citation
“…MPS VI was evaluated because it is among the rarest subtype worldwide yet is frequent in Brazil. The study was performed in Porto Alegre in 2007, and an estimated 65 patients were diagnosed with MPS VI in Brazil; of these, 38.5% showed the most common clinical characteristics of the disease . MPS VI shows autosomal recessive inheritance in the short arm of chromosome 5 (5q12‐13) and causes the absence of the lysosomal enzyme N‐acetylgalactosamine‐sulfatase, which functions in glycosaminoglycan degradation, namely dermatan sulfate (DS) and chondroitin sulfate (CS) …”
Section: Introductionmentioning
confidence: 99%